Solid-phase synthesis of structurally diverse heterocycles by an amide-ketone condensation/N-acyliminium Pictet-Spengler sequence - Givskov, Michael (2013)
An efficient approach for the solid-phase synthesis of structurally diverse heterocyclic compounds is presented. Under acidic reaction conditions, peptidic levulinamides undergo intramolecular ketone–amide condensation reactions to form cyclic N-acyliminium intermediates. In the presence of a tethered nucleophile, a second cyclization reaction results in the formation of a fused bicyclic ring system. The scope of the methodology was demonstrated by several combinations of substituted ketones and nucleophiles, the latter conveniently originating from amino acids with functionalized side chains, such as tryptophan, substituted phenylalanines, and cysteine. The cyclization sequence provides diastereomerically pure products in high yields. In one extension of the methodology, the resulting relative stereochemistry of the products enables the formation of bridged ring systems by a unique cyclative release mechanism.